Diversifikasi Transmisi Bahasa Agama Dalam Konteks Politik; Tinjauan Linguistik Strukturalis Terjemah Kata “Auliya’” - Muhammad Muchlis Huda; Syihabuddin Qalyubi; Ahmadi Ahmadi; Evi Muafiah Evi Muafiah; Mohammad Jailani (Department of Arabic Education - Faculty of Educational Sciences, 2023)
In the last few decades, especially after the fall of the New Order regime, the political constellation in Indonesia has been quite dynamic and tends to be populist. Many people consider that the populism aspirations of Muslims as the majority religion embraced by Indonesian citizens in several aspects of political life are experiencing a strengthening trend. One of the precedents that indicates the strengthening trend of Islamic populism is the case of blasphemy and the emergence of the 212 movement. This movement emerged after the 2017 DKI Jakarta election campaign where one of the candidate pairs at that time was suspected of insulting Islam by quoting Tarjamah Surah al-Maidah Verse 51 for pragmatic purposes of electoral politics. The question is, how do translation institutions in Indonesia that are considered authoritative translate this verse, especially the word